Compte-rendu: Metaphrasis in Byzantine Literature, ed. A. ALWIS - M. HINTERBERGER - E. SCHIFFER [Byzantioς. Studies in Byzantine History and Civilisation 17], Turnhout 2021 - LAMPADARIDI, Anna (Byzantina Symmeikta, 2022)
Compte-rendu: Metaphrasis in Byzantine Literature, ed. A. ALWIS - M. HINTERBERGER - E. SCHIFFER [Byzantioς. Studies in Byzantine History and Civilisation 17], Turnhout 2021